28-Day inhalation toxicity study with evaluation of lung deposition and retention of tangled multi-walled carbon nanotubes. Issue 2 (7th February 2020) - Kim, Jin Kwon; Jo, Mi Seong; Kim, Younghun; Kim, Tae Gyu; Shin, Jae Hoon; Kim, Boo Wook; Kim, Hoi Pin; Lee, Hong Ku; Kim, Hee Sang; Ahn, Kangho; Oh, Seung Min; Cho, Wan-Seob; et al.
Abstract: Lung deposition and retention measurements are now required by the newly revised OECD inhalation toxicity testing guidelines 412 and 413 when evaluating the clearance and biopersistence of poorly soluble nanomaterials, such as multi-walled carbon nanotubes (MWCNTs). However, evaluating the lung deposition concentration is challenging with certain nanomaterials, such as carbon-based and iron-based nanomaterials, as it is difficult to differentiate them from endogenous elements. Therefore, the current 28-day inhalation toxicity study investigated the lung retention kinetics of tangled MWCNTs. Male Sprague Dawley rats were exposed to MWCNTs at 0, 0.257, 1.439, and 4.253 mg/m 3 for 28 days (6 h/day, 5 days/week, 4 weeks). Thereafter, the rats were sacrificed at day 1, 7, and 28 post-exposure and the pulmonary inflammatory response evaluated by analyzing the bronchoalveolar lavage fluid. Plus, the blood biochemistry, hematology, and histopathology of the lungs were also examined. The lung deposition and retention of MWCNTs were determined based on the elemental carbon content in the lungs after tissue digestion. The number of polymorphonuclear cells and LDH concentration were both found to be significantly higher with the medium and high concentrations (1.439 and 4.253 mg/m 3 ) and dose dependent. The estimated retention half-life for the high concentration (4.253 mg/m 3 ) was about 35 days. The results of this study indicate that tangled MWCNTs seem to have a relatively shorter retention half-life when compared to previous reports on rigid MWCNTs, and the no-observed adverse effect level (NOAEL) for the tested tangled MWCNTs was 0.257 mg/m 3 in a previous rat 28-day subacute inhalation toxicity study.